Projected changes in sea ice and the navigability of the Arctic Passages under global warming of 2 ℃ and 3 ℃. (December 2022) - Chen, Jinlei; Kang, Shichang; You, Qinglong; Zhang, Yulan; Du, Wentao
Abstract: Although a rapid decrease in sea ice due to global warming has improved the navigable potential of the Arctic passages, the extent to which this area will become viable for commercial shipping in the future remains unclear. This study investigated the accessibility of the Northern Sea Route and Northwest Passage under global warming of 2 °C and 3 °C. We applied the Polar Operational Limit Assessment Risk Indexing System to measure navigability by considering the impacts of sea ice and ice resistance of ships. Except for the Parry Channel, surface air temperature is positive in the Seas along two passages in September under 2 ℃ warming. With global warming of 3 °C, the warming area extends northward, and the concentration of sea ice drops below 20%. The thickness of the sea ice is still substantial in the eastern Beaufort Sea and the waters within the Canadian Arctic Archipelago and north of Greenland, both of which can restricting the opening of the Arctic passages. Temperature increases cause sea ice to be younger and are more pronounced in the seas on the European side of the Arctic. The results indicate that changes in sea ice improve the navigability of the Arctic passages. Ships in Polar Class 6 may be unimpeded along two Arctic passages in November from 2 ℃ warming onward, whereas ordinary ships may be capable of passing the Northern Sea Route with global warming of 3 ℃, with maximum potential in September. This study provides an important reference for planning global shipping in the Arctic in the future, even with some uncertainty in the model projections.